2016
DOI: 10.2215/cjn.03760416
|View full text |Cite
|
Sign up to set email alerts
|

Decisions about Renal Replacement Therapy in Patients with Advanced Kidney Disease in the US Department of Veterans Affairs, 2000–2011

Abstract: In this large United States cohort of patients with advanced CKD, the majority received or were preparing to receive RRT. This was true even among the oldest patients with the highest burden of comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
64
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 24 publications
2
64
1
Order By: Relevance
“…The implementation of best clinical practices starts with a baseline assessment of the current state of services. That is what the study by Wong et al (15) in this issue of the Clinical Journal of the American Society of Nephrology provides. They describe the existing practice pattern of dialysis initiation in a distinct cohort from the US Department of Veterans Affairs (VA) and contextualize it with global trends.…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…The implementation of best clinical practices starts with a baseline assessment of the current state of services. That is what the study by Wong et al (15) in this issue of the Clinical Journal of the American Society of Nephrology provides. They describe the existing practice pattern of dialysis initiation in a distinct cohort from the US Department of Veterans Affairs (VA) and contextualize it with global trends.…”
mentioning
confidence: 65%
“…The failure to consider prognosis in dialysis decision making found in the study by Wong et al (15) has been shown before in United States nephrology practice. An interview study of 62 patients on chronic dialysis with high 1-year mortality noted that none of the patients reported a discussion of prognosis with their nephrologist, and in 60% of patients, nephrologists were unable to provide a prognostic estimate (18).…”
mentioning
confidence: 84%
See 3 more Smart Citations